Personalized Pathway-Activated Systems Imaging in Oncology : Principal and Instrumentation - Inoue, Tomio; Yang, David; Huang, Gang (Springer Singapore : Imprint: Springer, 2017)
This comprehensive volume covers radiopharmaceuticals developed for pathway-directed systems in imaging and theranostic applications. We now are at the cutting edge of providing personalized treatment with increased use in oncology of these new radiopharmaceuticals. Trends in high-resolution instrumentation development, quality assurance systems and regulatory compliance for radiopharmaceuticals, clinical evaluation of radiopharmaceuticals, and benefits and pitfalls of the current clinical FDG PET are discussed. Radiopharmaceuticals are used for diagnosis of diseases of the central nervous and cardiovascular systems and for staging, restaging, and treatment planning for cancers. Nuclear biomarkers allow precise measurement of molecular pathways on a whole-body image upon administration of functional radiolabeled agents, and nuclear imaging agents have potential use in patient selection, pharmacokinetic, dosage-finding, and proof-of-concept studies. Nuclear imaging agents and hybrid instrumentation also provide sensitive and specific answers for differential responsiveness in therapeutic outcome. This book serves as a reference for moving the discovery and development of radiopharmaceuticals from the workbench to clinical applications. It thus benefits not only clinicians but also translational research scientists-molecular biologists, chemists, imaging scientists, pharmaceutical developers, physicists, and support staff.
Keywords: Medicine.; Nuclear medicine.; Oncology.; elektronické knihy; electronic books